Bibliotherapy: Increasing Understanding of Religious Moderation with Group Counseling - Syaputra, Yogi Damai; Saputra, Randi; Monalisa, Monalisa; Ardini, Fadhila Malasari; Widiatmoko, Mualwi; Khairat, Imalatul; Ramanda, Peni; Gusman, Elvina (Bulletin of Counseling and Psychotherapy, 2024)
Extreme thoughts about moderate Islam are often the beginning of divisions. A shallow understanding of religious moderation makes it easier for someone to be indicated by radical views. Counselors have an essential role in increasing students' understanding of religious moderation. This study aims to improve students' understanding of religious moderation in public schools through group guidance using bibliotherapy techniques. This study used a quasi-experimental method with a Non-equivalent control group design. The sample of this research was 20 students, consisting of 10 students for each experimental and control group, per Gazda's (1969) recommendations regarding the adequate number of group guidance participants, ranging from 8 to 10 participants. The sample has filled out the Religious Moderation Scale (RMS) developed by Monalisa (2022) and is indicated to be in a low category. Data were analyzed using the Wilcoxon signed rank test to determine the effect before and after the intervention was given. Then, to find out the average difference between the experimental group and the control group, it was analyzed using the Mann-Whitney test. The study's results showed a difference in understanding of religious moderation before and after the intervention, with a significance of .005. The research results showed that the group guidance intervention using bibliotherapy techniques was effective in increasing students' understanding of religious moderation with a Z score of -3.885 and a significance value of .000.